Implementation of floating point adder and multiplier based on residue number system - Lim, Hue Hsean. (2012)
Floating point processor is part of computer system specially designed to execute floating point operations. Typical arithmetic operations are addition, subtraction, multiplication and division. Today, it can be seen that most of the floating point processors are implemented using the weighted number system representation such as binary or decimal. However, their overall operating speed is limited by the carry propagation delay involved in arithmetic operations.